Luxembourg : Financial Sector Assessment Program: Detailed Assessment of Observance-Assessment of Observance of the CPSS-IOSCO Principles for Financial Market Infrastructures: Clearstream Banking Luxembourg. (IMF Staff Country Reports; Country Report, 2017)
This report assesses the risk management practices of Clearstream Banking Luxembourg (CBL) based on the Committee on Payment and Settlement Systems-International Organization of Securities Commissions (CPSS-IOSCO) Principles for Financial Market Infrastructures. The findings reveal that a range of principles are in broad observance. A key priority is to reduce CBL dependence on commercial banks in its daily operations. There is significant dependence on a limited number of depository and cash correspondent banks, in particular for the US and UK markets. This dependence could be actively mitigated through an increase in the number of contracted banks or, where possible, the establishment of direct links with local central securities depositories and central banks.